2020
DOI: 10.1007/s00425-020-03454-7
|View full text |Cite
|
Sign up to set email alerts
|

An efficient virus-induced gene silencing (VIGS) system for functional genomics in Brassicas using a cabbage leaf curl virus (CaLCuV)-based vector

Abstract: Background: Virus-induced gene silencing (VIGS), a posttranscriptional gene silencing method, represents an effective technology for the analysis gene functions in plants. However, no VIGS vectors are available for Brassica oleracea till now. The gene silencing vectors TRV, pTYs and CaLCuV were chose to improve the VIGS system in cabbage, using phytoene desaturase (PDS) gene as an efficient visual indicator for VIGS. Results: We successfully silenced the expression of PDS and observed the photobleaching phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 67 publications
1
5
0
2
Order By: Relevance
“…Notably, the most commonly used agroinfiltration method for VIGS is the syringe infiltration of leaves. This methods has been applied in VIGS studies on a broad range of plant species: Brassica oleracea [ 3 ], Gerbera hybrid [ 45 ], Solanum lycopersicum [ 46 ], lettuce [ 47 ], Oryza sativa [ 48 ], Triticum aestivum [ 31 ], Eschscholzia californica [ 49 ], Capsicum annuum [ 50 ], Gossypium hirsutum [ 51 ]. In sunflower [ 38 ], using syringe infiltration, the authors observed the photo-bleaching phenotype in expanded leaves and leaflets near the inflorescence.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Notably, the most commonly used agroinfiltration method for VIGS is the syringe infiltration of leaves. This methods has been applied in VIGS studies on a broad range of plant species: Brassica oleracea [ 3 ], Gerbera hybrid [ 45 ], Solanum lycopersicum [ 46 ], lettuce [ 47 ], Oryza sativa [ 48 ], Triticum aestivum [ 31 ], Eschscholzia californica [ 49 ], Capsicum annuum [ 50 ], Gossypium hirsutum [ 51 ]. In sunflower [ 38 ], using syringe infiltration, the authors observed the photo-bleaching phenotype in expanded leaves and leaflets near the inflorescence.…”
Section: Discussionunclassified
“…Virus-Induced Gene Silencing (VIGS) has emerged as a powerful tool in many areas of crop research, including functional gene analysis [ 1,2,3 ], pathogen resistance studies [4, 5, 6 ], abiotic stress tolerance [ 7, 8, 9 ], and general crop improvement [ 10 ]. The number of search projects dedicated to the VIGS technology is booming, highlighting its widespread adoption and recognition as a versatile tool for advancing crop science and biotechnology.…”
Section: Introductionunclassified
“…CaLCuV-based GIGS involved the use of Agrobacterium and was relatively inexpensive and had a higher batch efficiency target. This geminiviral vector system has also been said to be equally efficient in other Brassica species, B. rapa, and B. nigra, and therefore a potent functional genomic tool for crop plants (Xiao et al, 2020).…”
Section: Efficient Gene Silencing Vector Systemsmentioning
confidence: 99%
“…Moreover, Brassica oleracea is also considered to be a model for the study of the genomic evolution of Brassica species due to its typical diploid genome structure [ 26 ]. The molecular mechanisms underlying many significant biological processes, including pigment accumulation [ 27 ], self-incompatibility [ 28 ], and flowering [ 29 ], have been dissected in Brassica oleracea , while a lot of classic biotechnologies, including virus-induced gene silencing (VIGS) [ 30 ] and CRISPR/Cas9-based gene editing [ 31 ], have also been applied in Brassica oleracea . Thus, the discovery of functional genes in Brassica oleracea is required for the genetic improvement of desired traits by the most advanced molecular breeding strategies.…”
Section: Introductionmentioning
confidence: 99%